Reformulate Supervisory Mechanism of The Indonesian Corruption Eradication Commission, Why and How? - Ahmad Sahroni; Mohammad Hazyar Arumbinang (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
Supervision of the Indonesian Corruption Eradication Commission needs to be reformed. This is to prevent the KPK from abusing its authority in the process of eradicating corruption. In addition, reforms also need to be carried out to increase accountability, ensure transparency, build public trust, and prevent internal corruption. Specifically, improvements to the KPK's supervision method in this study will focus on efforts to improve the filling of the KPK Supervisory Board position. The research method using Normative Juridical Legal Research, with a Conceptual Approach and a Statute Approach. The results of the study show that the KPK supervision carried out by the KPK Supervisory Board shows less than optimal results. This claim is due to the filling of the KPK Supervisory Board position which only comes from the President. There is no Checks and Balances mechanism in filling the Supervisory Board position. The author recommends that the DPR can take and increase its role in filling the KPK Supervisory Board position. In addition, there are several other reformulations of improvements. Including the implementation of reports and complaints with a reverse proof system, as well as building an information system for alleged ethical violations.